Exploring the spatial distribution of social impacts in protected areas - Jones, Nikoleta; Begley, Alfie; Malesios, Chrysovalantis; Svajda, Juraj; McGinlay, James; Dimitrakopoulos, Panayiotis G. (Frontiers in Environmental Science, 2023)
1. Protected Areas (PAs) are the most widely applied tool for biodiversity conservation. The primary role of these areas is to protect and restore ecosystems, but it has become increasingly evident that in order to designate effective PAs it is also crucial to take into consideration how they contribute to sustainable local socioeconomic targets. In the past decade studies focusing on social impacts of PAs have increasingly studied a number of impacts such as on people's quality of life, income and connectedness to nature.2. Although the literature on social impacts of PAs has increased there is limited evidence regarding the distribution of these impacts across different locations inside and near PAs. Addressing this gap is useful for practitioners considering that it is now widely accepted that social impacts are a significant predictor for the level of public support for PA.3. In the current study we explore this topic and analyse the spatial distribution of perceived social impacts in 4 European Protected Areas using primary data from 1251 households. We apply a new modeling framework using Bayesian statistics revealing that social impacts are often unevenly distributed between local communities and extend outside the boundaries of a PA. 4. Our analysis also shows that spatial proximity with other people (what are the perceptions of people who live nearby) is more important for predicting most perceived social impacts of PAs compared to how close respondents are to a PA. Our results highlight that social impacts may be geographically unevenly distributed in PAs and we present a new way of measuring the spatial distribution of these impacts which can be useful for national park authorities and in general managers of PAs.